1996
DOI: 10.1002/pc.10676
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of mechanical properties of recycled fiberglass reinforced polyamide 66

Abstract: An experimental study of the mechanical performance of in‐plant recycled fiberglass reinforced polyamide 66 is reported. The fiber length distributions were used to investigate and to predict the influence of process induced fiber shortening on the short term performance of recycled samples compared to that of virgin samples. The results indicate that fiber shortening has a strong influence on strength. Applying a modified Kelly‐Tyson model to the fiber length distribution gave excellent agreement with measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…where is the fibre strength and τ ∗ is the interfacial shear strength, r is radius of the fibre. The critical fibre length is estimated to be 204 μm, using the = 3500 MPa, r = 3.5 μm, τ ∗ = 60 MPa which are typical values for CF reinforced composites 35 . The reinforcing effect of the fibres increases with their lengths, which are supposed to be exceeding l c as much as possible to obtain high strength.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…where is the fibre strength and τ ∗ is the interfacial shear strength, r is radius of the fibre. The critical fibre length is estimated to be 204 μm, using the = 3500 MPa, r = 3.5 μm, τ ∗ = 60 MPa which are typical values for CF reinforced composites 35 . The reinforcing effect of the fibres increases with their lengths, which are supposed to be exceeding l c as much as possible to obtain high strength.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanical properties of CF reinforced composites are largely affected by the volume fraction of fibres, fibre length distribution and the interfacial shear strength between fibres and matrix 35 . This paper establishes a modified Kelly-Tyson model 35 36 37 for predicting the tensile strength of the CF/PA12/EP ternary composites, taking into account the effects of fibre lengths as well as fibre-matrix interface. As to a ductile matrix and large strains in the composites, a linear increase of tensile stress in the fibre with distance from the ends can be assumed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, the composite stress σ C at given strain ε C is given by [6,14] (4) where τ and σ m are the average fiber/resin interfacial shear stress and stress in the resin, respectively, V i denotes volume fraction of fiber with the length l i and l C represents the critical fiber length given by…”
Section: Macromechanical Modelmentioning
confidence: 99%
“…Thomason [14,15] has discussed the effect of fiber length distribution on the mechanical properties in short glass-fiber reinforced composites. Eriksson et al [6] has reported the mechanical properties of recycled glass-fiber reinforced polyamide resin and predicted the strength based on the Kelly-Tyson model [5].…”
Section: Introductionmentioning
confidence: 99%